The Effect of Soil on the Biochemical Plasticity of Berry Skin in Two Italian Grapevine (V. vinifera L.) Cultivars - Perin, Corrado; Fait, Aaron; Palumbo, Fabio; Lucchin, Margherita; Vannozzi, Alessandro (Frontiers in Plant Science, 2020)
Grapevine represents a particularly interesting species as concerns phenotypic plasticity, considering that the terroir, meaning the contribution of the geography, geology, and climate of a certain place, together with the agronomical practices utilized, may deeply influence the berry phenotype at the physiological, molecular, and biochemical levels. This phenomenon leads to the production of wines that, although produced from the same variety, exhibit different enological profiles and represents an issue of increasing interest from both a biological and an economic point of view. The main objective of the present study was to deepen the understanding of phenotypic plasticity in grapevine, trying to dissect the role of one its important components – the soil – by investigating the singular effect that different physico-chemical soil properties can produce in terms of berry plasticity at the phenological, physiological, and biochemical levels in a red and a white variety of great economic importance in Italy and overseas: Corvina and Glera. The results indicated a genotype-dependent response to the soil factor, with higher biochemical plasticity in Corvina with respect to Glera and suggested a key role of specific soil properties, including the skeleton, texture, and mineral composition, on the metabolite profile of berry skin.